Transition Metal‐Free Direct Electrochemical Carboxylation of Organic Halides Using a Sacrificial Magnesium Anode: Straightforward Synthesis of Carboxylic Acids - Iryna Lesko; Stéphane Sengmany; Raphaël Beltran; Erwan Le Gall; Eric Léonel (ChemistryOpen)
Abstract The direct electrochemical carboxylation of aryl, benzyl and alkyl halides by CO2 is described using a magnesium anode and a nickel foam cathode in an undivided cell. The process employs a sacrificial anode and does not require the additional use of a transition metal catalyst or demanding conditions, as the reactions are carried out under galvanostatic mode, at −10 °C and with commercial DMF. Under these operationally simple conditions, an important range of carboxylic acids are affordable. Mechanistic investigation account for the in situ generation of a carbanionic species that is not a simple organomagnesium halide.